Speech Acts in Text Dialogues: An Analysis of English Textbook Merdeka Belajar for Junior High School - Fitriani, Fitriani; Hidayat, Didin Nuruddin; Husna, Nida; Alek, Alek (English Education: Jurnal Tadris Bahasa Inggris, 2023)
This study aims to investigate the types of speech acts and their functions contained in the dialogues of the English textbook titled "English in Mind Second Edition Students' Book Starter Grade VII," which was composed based on the implementation of Kurikulum Merdeka Belajar. The study employed a descriptive qualitative research approach, utilizing text dialogues from the English textbook as the primary data source. The speech acts in the dialogues were analyzed based on Searle's (1976) speech act framework. The results indicate a total of 161 speech acts (utterances) across all dialogues in the textbook. The distribution of speech acts is as follows: assertive accounted for 29.2% (47 instances), directive accounted for 24.8% (40 instances), commissive accounted for 9.9% (16 instances), expressive accounted for 35.4% (57 instances), and declaration accounted for 0.6% (1 instance). While the textbook demonstrates good representation of speech acts within Searle's framework, it should be noted that certain functions of speech act types, specifically commissive and declarative speech acts, were not consistently present in all dialogues. Based on these findings, this study suggests that textbook designers and material developers strive to authentically incorporate various functions of speech act types, ensuring authentic interactions and natural language usage. By doing so, they can enhance EFL learners' performances and interactions using speech acts. Please note that this revised version is based on the feedback and suggestions provided earlier. It aims to address the structural and grammatical aspects and provide a clearer representation of the information presented in the abstract